Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.5194/nhess-23-1095-2023
|View full text |Cite
|
Sign up to set email alerts
|

Multi-event assessment of typhoon-triggered landslide susceptibility in the Philippines

Abstract: Abstract. There is a clear need to improve and update landslide susceptibility models across the Philippines. This is challenging, as landslides in this region are frequently triggered by temporally and spatially disparate typhoon events, and it remains unclear whether such spatially and/or temporally distinct typhoon events cause similar landslide responses, i.e. whether the landslide susceptibility for one typhoon event is similar for another. Here, we use logistic regression to develop four landslide suscep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Unimpeded by cloud cover, Sentinel‐1 resolves landslide timing much better than previous approaches based on optical imagery. Beyond Nepal and monsoon‐affected areas, the method could be applied to any landslide inventory in vegetated environments whose timings are poorly constrained and thus difficult to assign to a specific trigger, for example, landslides triggered during sequences of storms or earthquakes, including post‐seismic rainfall‐triggered landsliding (Amatya et al., 2023; Ferrario, 2019; Jones et al., 2023). Our study thus highlights the value that Sentinel‐1 could have in disentangling the effects of multiple landslide‐triggering events in cloudy conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Unimpeded by cloud cover, Sentinel‐1 resolves landslide timing much better than previous approaches based on optical imagery. Beyond Nepal and monsoon‐affected areas, the method could be applied to any landslide inventory in vegetated environments whose timings are poorly constrained and thus difficult to assign to a specific trigger, for example, landslides triggered during sequences of storms or earthquakes, including post‐seismic rainfall‐triggered landsliding (Amatya et al., 2023; Ferrario, 2019; Jones et al., 2023). Our study thus highlights the value that Sentinel‐1 could have in disentangling the effects of multiple landslide‐triggering events in cloudy conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Landslide triggers can be attributed to loading, slope geometry, weather conditions, and hydrological conditions (Perkins et al, 2024;Van Natijne et al, 2023;Millán-Arancibia and Lavado-Casimiro, 2023;Jones et al, 2023). Among these, hydrological conditions, especially groundwater levels, have been one of the most critical elements considered in studies related to landslide prediction (see Figure 1).…”
Section: Groundwater Levels and The Forecasting Of Deep-seated Displa...mentioning
confidence: 99%
“…In addition, the LASSO algorithm serves the purpose of autonomously identifying the pivotal independent predictor variables essential for effectively classifying the response of the dependent variable [27].…”
Section: Least Absolute Shrinkage and Selection Operator (Lasso)mentioning
confidence: 99%
“…The findings revealed that the RF algorithm exhibited the highest performance, followed by the ANN algorithm, while SVM and Naive Bayes classifiers demonstrated comparatively poor results. Likewise, Jones et al [27] used logistic regression to develop four landslide susceptibility models based on 3 typhoon-triggered landslide inventories between 2009 and 2019.…”
Section: Introductionmentioning
confidence: 99%